Searching for an ideal post graduate supervisor: exploring Malaysian students' experience towards supervisory relationship - Murshid, Siti Fairuz; Ismail, Ismi Arif; Baki, Roselan (Human Resource Management Academic Research Society, 2019)
This study explores the experience of establishing a supervisory relationship between post-graduates and supervisors from the perspective of four first semester graduate students in one of Malaysia public university. This study uses a qualitative case study design. Data are obtained through semi-structured interviews and document analysis. The findings of this research revealed that the adjustment aspect of alignment of tendency and interests, confidence, meaningful communication, high reliability, mutual respect and punctuality were the key determinants of establishing a positive supervisory relationship between post graduates and supervisors. This study also demonstrated that a healthy rapport between post graduate students and supervisors really do support their research and learning journey. Respondents also agree that students should not rely solely on supervisors, because the true reason on the success of quality thesis writing is fully under the post graduates’ own accountability and responsibility.